The Role of Digital Technology in Realizing the Sustainable Development Goals (SDGs) - Soelistianto, Farida Arinie; Muthmainah, Hanifah Nurul (Westscience Press, 2025)
Digital technology has increasingly become a strategic instrument in accelerating the achievement of the Sustainable Development Goals (SDGs), particularly in developing countries such as Indonesia. This study aims to examine the role of digital technology in supporting the achievement of SDGs in Indonesia using a quantitative research approach. Data were collected from 85 respondents through a structured questionnaire measured using a Likert scale. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25, employing descriptive statistics, validity and reliability testing, and simple linear regression analysis. The results indicate that digital technology has a positive and statistically significant effect on SDG achievement, with digital technology explaining 50.7% of the variance in sustainable development outcomes. These findings suggest that increased utilization of digital platforms and systems contributes to improved economic efficiency, social inclusion, and sustainable development practices. This study provides empirical evidence on the importance of digital transformation in achieving SDGs and offers practical insights for policymakers and stakeholders to strengthen digital-based development strategies in Indonesia